Breakup of multiple jets in immiscible liquid-liquid systems: A computational fluid dynamics study - Pareek, Vishnu; Parmar, Harisinh Bhikhubhai; Phan, Chi; Evans, G. (Engineers Australia, 2011, 2011)
Hydrodynamic behavior of immiscible liquid-liquid systems has great importance in many industrial operations such as mining, food, cosmetics and pharmaceuticals industries. This behavior governs jet formation and breakup, droplet formation and coalescence in emulsification. For successful emulsion applications, it is very important to generate small and uniform droplets to ensure product stability. In addition, the breakup of the jet increases the interfacial area and hence enhances efficiency of processes such as heat transfer, mass transfer and sometimes chemical reactions. In this study, the formation of droplets from multiple circular nozzles into an immiscible liquid was studied using computational fluid dynamics (CFD). The unsteady motion of the interface separating two immiscible fluids is followed by solving the Navier–Stokes equations for incompressible and Newtonian fluids with a volume of fluid (VOF) method. Most significantly, the interaction between neighboring jets was modelled for micro-jet condition.